Study on Water Absorption and Thermal Conductivity of Tunnel Insulation Materials in a Cold Region under Freeze-Thaw Conditions - Youyun Li; Huan Wang; Li Yang; Shiqiang Su (Advances in Materials Science and Engineering)
A thermal insulation layer is often deposited on the lining structure of tunnels in cold regions to solve the problem of frost damage. When the air humidity in the tunnel becomes excessively high, the thermal insulation material tends to absorb water, leading to significant changes in thermal conductivity. Moreover, the temperature differences between the day and night cycles have been observed to be significant in portal sections of cold region tunnels, which facilitate the freeze-thaw cycle and, consequently, deteriorate the performance of the thermal insulation material. Therefore, the purpose of this study is to determine the changes in the water absorption, thermal conductivity, and microstructure of polyurethane and polyphenolic insulation boards under freeze-thaw conditions. To this end, an indoor water absorption test was conducted for both the insulation boards till they were saturated, which then underwent a freeze-thaw cycle test. It was determined that the water absorption and thermal conductivities of these boards increased linearly with the number of freeze-thaw cycles. In order to explore the change of thermal conductivity of thermal insulation materials after moisture absorption, this study provides insights into the relationship between the thermal conductivities and water contents of tunnel insulation materials under normal and freezing temperatures.